Response of High School Students in Learning Arabic Through Online - Rosa Annisa; Doni Septi (Indonesian Journal of Islamic Studies, 2022)
At the beginning of the entry of the Covid-19 virus in Indonesia in March 2020, it was known that 2 Indonesian citizens were exposed to the Covid-19 virus. This made the government decide to hold learning from home for all educational institutions. Thus, this study was conducted to determine student responses to learning Arabic through online. The student's response to learning Arabic through online is that students are not happy with learning Arabic through online because Arabic is a foreign language where learning is more effective face-to-face. Applications that are often used by teachers in learning Arabic through online are Zoom and Google Meet to deliver material, Quipper and Google Classroom to provide practice questions. Student learning outcomes are more effective offline learning than online learning because offline learning is easier to understand, the time is longer and the material can be explained in detail and the teacher is more flexible and more effective in delivering the material. Keywords - Student Response and Online Learning.